Early Cretaceous tectono-sedimentary evolution of the southwestern margin of the Bisbee basin - Carlos Manuel González-León (Revista Mexicana de Ciencias Geológicas)
The Bisbee basin is considered to be the primary structural site of sedimentation of the Bisbee Group of Late Jurassic and Early Cretaceous age, in the region of southeastern Arizona and southwestern New Mexico in the U.S.A. and northeastern Sonora in Mexico. Recent studies, however, have confirmed the presence of correlative lithostratigraphic units of the Bisbee Group in several areas of northem and central Sonora, which indicate that the Bisbee basin extended southward of the previously defined boundaries.